An Extremely Rare Bile Leakage: Aberrant Bile Duct in Left Triangular Ligament (Appendix Fibrosa Hepatis) - İhsan Yıldız; Yavuz Savaş Koca; Sezayi Kantar (Case Reports in Surgery)
Background. The anatomical variability of bile ducts can leave surgeons in very difficult conditions.Ultrasonography, computed tomography, magnetic resonance imaging (MRCP) and endoscopic imaging methods are used in diagnosis. In addition to conservative approaches, endoscopic procedures and laparoscopic or open surgical interventions may be necessary for treatment. In this article, we present a case of aberrant bile duct in left triangular ligament (appendix fibrosa hepatis), which is rarely seen. Case. We report the case of a 67-year-old female patient who was operated on due to dumping syndrome symptoms and hiatal hernia. There was a drainage of bile from the left side of the liver which was placed under the cardioesophageal junction. MRCP found bile esophageal in the left triangular ligament of the liver. Aberrant bile ducts were found in the left triangular ligament and ligated. The patient was discharged on the 7th day after operation. Conclusion. The anatomical variability of bile ducts can leave surgeons in very difficult conditions. We recommend that the dissected left triangular ligament should be ligated for the aberrant bile duct, especially in female patient.